Os movimentos dos cursos técnicos subsequentes sobre os sentidos do trabalho: a (des)alienação dos trabalhadores-estudantes - Almeida, Ana Paula de (2019)
This study is situated in the research area of “Labor and Education” linked to the Research Line “Policies and Management in Vocational and Technological Education” of the Postgraduate Program in Vocational and Technological Education (PPGEPT), of the Industrial Technical School of Santa Maria (CTISM), developed in the research group “Transformation - Study and Research Group on Policies and Pedagogical Work in Vocational Education”. The main objective is to analyze the movement that Subsequent Technical Courses produce to studentworkers perception, from the Subsequent Technical Courses of the IFRS-Campus Ibirubá, on the meanings of work. Therefore, this research aims to describe the characteristics of Student- Workers enrolled in the IFRS-Campus Ibirubá Subsequent Technical Courses, classes of 2017/2018, to analyze the offer of these by the Federal Institutes (FIs) in Brazil, starting in the decade of 1990, also as to identify the perceptions of Student-Workers about work, analyzing the meanings of work that emerge in the formative trajectory of the Subsequent Technical Courses. This study was born from the trajectory of the researcher as Social Worker in the researched Campus and it is based on the Historical-Dialectical Materialism (HDM). To the research subjects, Student-Workers of Subsequent Technical Courses, classes of 2017/2018, it was applied as research tools, an on-line questionnaire with open and closed questions: Focus Groups and Interlocution Group, permeated by the Field Journal, in view of the strategies for data productions and the correspondent documental and bibliographical analysis. The recorded, transcribed and categorized manifestations were used throughout the text for analysis and dialectic writing. The results of this study show that the movement of the Subsequent Technical Courses, regarding the work of student-workers, converges with the perspective of alienated work, while the process of (de)alienation of work occurs within the restricted space between individual and collective work, hence the necessity of rethinking about the curricular practical possibilities coherent with the identity of the FIs at the present moment, especially regarding to the senses of the Subsequent Courses.